Comparing the ecological consequences of globally invasive fishes versus their F1 hybrids in recreational fisheries - Ali Serhan Tarkan; Irmak Kurtul; J. Robert Britton (NeoBiota)
Recreational angling is a major introduction pathway for non-native fish into freshwaters, where multiple non-native fishes are often released into waterbodies to diversify the angling opportunities. When these non-native fishes are taxonomically similar, then there is concern that their hybridisation will result in F1 generations comprising of novel phenotypes that outperform their parental species, resulting in the impacts of these ecological engineering species being accelerated. Across two water temperatures (18 °C, 26 °C), comparative functional response analyses (CFR) quantified the consumption patterns of the globally invasive freshwater fish common carp Cyprinus carpio and goldfish Carassius auratus, plus their F1 hybrids, before testing differences in their specific growth rates (SGRs). In CFRs, carp consumed significantly more prey at 18 °C than the other fishes, and with no differences between any of the fishes at 26 °C. SGRs also did not differ substantially between the fishes at either temperature. These results suggest that hybridisation between the high impacting parental species did not produce novel phenotypes of high ecological performance that could accelerate their ecological impacts in invaded ecosystems. Accordingly, the ecological risks of their use in recreational angling remain an issue that is primarily associated with the parent populations, and this can be reflected in their invasion management.